As bonecas biônicas: a emergência das categorias transexual e travesti no Brasil na era farmacopornográfica - Hubner, Eduardo (2021)
This work target to analyze the categories transvestite and transsexual, taking into account the Brazilian historical process, from the pharmacopornographic era. The dissertation takes transsexuality and transvestite as an effect of the sexuality device, the product of a biopower government, operationalized through pharmacopower and pornopower. With this, it is sought to maintain that the transvestite category is the result of technological and pharmacological incorporation as part of a process of auto–guinea pig of pharmacopower and pornopower in the Brazilian context from the 1970 ages. The social, cultural, political and technological transformations that emancipated the category, in which a group of homosexuals known as fagots / dolls in the age 1950, incorporated these elements, as a way of transforming the body and identity. I also sought to discuss the institutional and legal processes that permeated the transsexual category and its consequences in Brazilian society in contrast to transvestites. Finally, I establish that the transvestite and transsexual categories are interdependent on cultural, social, economic and technological processes in the contingency of resistance and marginalization of each society.